Phytochemical study on Meiogyne Virgata Blume Miq. (annonaceae) / Abd. Rashid Li - Li, Abd. Rashid (2007)
Meiogyne virgata is a rain forest tree which grows in Peninsular Malaysia, Borneo, Java and Sumatera. Temuan clans in Peninsular Malaysia call it "Cha ngut". Its fruits are poisonous. There is no formal report on the traditional uses of this plant. However, Tadic et al, (1986) reported the isolation of isoquinoline alkaloids and triterpenes possessing important biological activities from stem barks and leaves of M. virgata collected from Mount Kinabalu, Sabah. It was suggested that this plant may be useful medicinally.